Substitute: The Untold Narrative of a Mother & Son- Abdullah M.I. Syed - Syed, Abdullah M.I. (New South Wales; Fairfield City Museum & Gallery, 2016)
Exhibition catalog. Essay: Zarmeene Shah
English
Keywords: N4390-5098 Visual Arts- Exhibitions; Personal archives; Pakistan